Managing Global Growth Risks and Commodity Price Shocks : Vulnerabilities and Policy Challenges for Low-Income Countries. (Policy Papers; Policy Paper, 2011)
As part of its work to help low-income countries (LICs) manage volatility, the IMF has recently developed an analytical framework to assess vulnerabilities and emerging risks that arise from changes in the external environment (see IMF, 2011a). This report draws on the results of the first Vulnerability Exercise for LICs (VE-LIC) conducted by IMF staff using this new framework. The report focuses on the risks of a downturn in global growth and of further global commodity price shocks, and discusses related policy challenges. The report is organized as follows: Chapter I reviews recent macroeconomic developments, including the spike in global commodity prices earlier this year. Chapter II assesses current risks and vulnerabilities, including how a sharp downturn in global growth and further commodity price shocks would affect LICs. Chapter III discusses policy challenges in the face of these risks and vulnerabilities.